2014
DOI: 10.1111/obr.12200
|View full text |Cite
|
Sign up to set email alerts
|

Will smaller plates lead to smaller waists? A systematic review and meta‐analysis of the effect that experimental manipulation of dishware size has on energy consumption

Abstract: It has been suggested that providing consumers with smaller dishware may prove an effective way of helping people eat less and preventing weight gain, but experimental evidence supporting this has been mixed. The objective of the present work was to examine the current evidence base for whether experimentally manipulated differences in dishware size influence food consumption. We systematically reviewed studies that experimentally manipulated the dishware size participants served themselves at a meal with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 15 publications
7
107
2
1
Order By: Relevance
“…However, there may of course be specific contexts or study designs which are conducive to dishware size influencing food consumption. For example, it may be the case that plate or bowl size only influences food intake if consumers are not allowed to serve themselves multiple times and refill their plate or bowl (10,11) . Further work testing this and identifying the conditions in which dishware size does v. does not influence food consumption would now be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there may of course be specific contexts or study designs which are conducive to dishware size influencing food consumption. For example, it may be the case that plate or bowl size only influences food intake if consumers are not allowed to serve themselves multiple times and refill their plate or bowl (10,11) . Further work testing this and identifying the conditions in which dishware size does v. does not influence food consumption would now be useful.…”
Section: Discussionmentioning
confidence: 99%
“…There are, of course, other plausible explanations which might explain why most studies have not replicated the previously reported dishware size effects on food intake. One is that earlier studies in this field tended to be conducted in field settings and because of this may be more likely to have potential methodological limitations or flaws (see Robinson et al (10) for a discussion).…”
mentioning
confidence: 99%
“…We note that while some previous reviewers focused on amount consumed (Libotte et al 2014;Robinson et al 2014b), they did appear to include some studies measuring amount self-served (e.g., Van Ittersum and Wansink 2013).…”
Section: Data Extractionmentioning
confidence: 99%
“…First, and in line with Robinson et al (2014b), we distinguish between manipulation of area whether reported as diameter (e.g., Rolls et al 2007) or area (e.g., Koh 2. We excluded studies that manipulated the size and number of containers simultaneously.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation